2016
DOI: 10.1097/mbp.0000000000000158
|View full text |Cite
|
Sign up to set email alerts
|

Elevated blood pressure in the emergency department

Abstract: A vast majority of ED patients with persistently elevated BP did not receive BP counseling and referral for further evaluation of elevated BP, suggesting lack of adherence to American College of Emergency Physicians policy recommendations in the assessment of ED patients with asymptomatic elevated BP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 11 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…[11] Previous studies have repeatedly shown scarce levels of physician adherence to hypertension treatment guidelines in various situations. [12][13][14] In addition, there is a gap between primary healthcare physicians (PCPs) awareness of hypertension treatment guidelines and their actual practice. [15,16] A cross-sectional study by Lautenberg et al on 264 Dutch general practitioners found that most respondents had positive attitudes towards local hypertension practice guidelines, yet physicians perceived adherence to guidelines varied widely across recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Previous studies have repeatedly shown scarce levels of physician adherence to hypertension treatment guidelines in various situations. [12][13][14] In addition, there is a gap between primary healthcare physicians (PCPs) awareness of hypertension treatment guidelines and their actual practice. [15,16] A cross-sectional study by Lautenberg et al on 264 Dutch general practitioners found that most respondents had positive attitudes towards local hypertension practice guidelines, yet physicians perceived adherence to guidelines varied widely across recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…We only found one other study, a retrospective review of the quality of hypertension treatment in the emergency department, that simultaneously measured pain and BP. 19 Although they found no relationship between severity of pain and initial BP, 19 the study was limited to patients with elevated blood pressure and so is not directly comparable.…”
Section: Discussionmentioning
confidence: 97%
“…Adherence of doctors to clinical guidelines has been studied in various situations [15, 24, 25], however, their adherence to hypertension guidelines remain scarce. In Sudan, this is the first documented study that measures adherence of doctors to hypertension guidelines in line with the local and international guidelines.…”
Section: Introductionmentioning
confidence: 99%